Kaji Eksperimental Pengaruh Subtitusi Etanol Pada Biosolar B20 Terhadap Kinerja Mesin Diesel - Teddi Febriardi Mulia; Romy Romy; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The scarcity of fuel has led to research is done to develop and utilize renewable fuel sources such as ethanol. The purpose of this study was to obtain and compare the performance of a Diesel Engine using B20 biosolar fuel and a Biosolar-Ethanol mixture. The alcohol compound used was 96% ethanol and mixed according to the different composition. The performance characteristics are carried out by testing diesel engines at a constant speed of 2100 rpm and load varied from 350 W, 700 W, 1000 W, 1350 W, 1700 W, 2000 W, 2350 W, 2700 W, and 3000 W. From the experimental results, the performance of diesel engines with ethanol substitute fuel has not changed in power, torque, and bmep. The thermal efficiency of biodiesel was 18.23% and the thermal efficiency of the 5% ethanol mixture was 15.74%, in the mixture of 10% by 16.90%, in the mixture of 15% at 20.16% and in the mixture of 20% by 20.11%.Keywords: Ethanol, biosolar, diesel engine, performance